2021
DOI: 10.1002/cam4.4197
|View full text |Cite
|
Sign up to set email alerts
|

Smoking status combined with tumor mutational burden as a prognosis predictor for combination immune checkpoint inhibitor therapy in non‐small cell lung cancer

Abstract: Background This study aimed to explore the prognostic value of tumor mutational burden (TMB) combined with smoking status in advanced non‐small cell lung cancer (NSCLC) patients who received immune checkpoint inhibitor therapy (anti PD‐1/PD‐L1 therapy) combined with chemotherapy or anti‐angiogenesis therapy. Methods We conducted a retrospective analysis of NSCLC patients who underwent next‐generation sequencing test (either 295‐gene panel NGS or 1021‐gene panel NGS) from September 2017 to November 2020. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…Multiple studies have confirmed that in patients with lung cancer undergoing systemic immune checkpoint inhibitor (ICI) therapy, those who smoke have an increased survival and better response rate to ICI compared with nonsmokers. Proposed mechanisms include increased programmed cell death ligand 1 expression and increased tumor mutational burden in non–small cell lung tumors of smokers . In patients with melanoma, the reports of smoking and response to ICI are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have confirmed that in patients with lung cancer undergoing systemic immune checkpoint inhibitor (ICI) therapy, those who smoke have an increased survival and better response rate to ICI compared with nonsmokers. Proposed mechanisms include increased programmed cell death ligand 1 expression and increased tumor mutational burden in non–small cell lung tumors of smokers . In patients with melanoma, the reports of smoking and response to ICI are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the chronic inflammation of the pulmonary system because of cigarette smoking has been thought to be associated with an immunosuppressive tumor microenvironment in LUAD 28 . In comparison with nonsmoker patients, an increased mutational burden was shown to enhance the sensitivity to immune checkpoint inhibitors in NSCLC patients with smoking history 29 . A higher mutational burden has been correlated with a favorable response in NSCLC patients who received anti‐PD‐1 therapy 30 .…”
Section: Discussionmentioning
confidence: 99%
“…28 In comparison with nonsmoker patients, an increased mutational burden was shown to enhance the sensitivity to immune checkpoint inhibitors in NSCLC patients with smoking history. 29 A higher mutational burden has been correlated with a favorable response in NSCLC patients who received anti-PD-1 therapy. 30 In this study, AIM2 upregulation is dominant for LUAD derived from The intracellular inflammatory responses have been highly correlated with the metastatic progression in many types of cancer.…”
Section: Aim2 Upregulation Potentiates the Expression Of Pd-l1 In Smo...mentioning
confidence: 99%
“…For example, it is known that cigarette smoking is one of sources of chronic inflammation [ 4 ], which might in turn lead to chronic obstructive pulmonary disease (COPD) or cancer. Cigarette smoking has been also linked to differences in response to immunotherapy [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Thus, in order to better understand the process of emergence of lung diseases, it is important to develop computational approaches, which, while leveraging existing data, can help to untangle the impact of various factors on molecular changes in lung tissue.…”
Section: Introductionmentioning
confidence: 99%